Research on Named Entity Recognition Based on Model Fusion. Issue 1 (1st July 2022) - Shi, Xueying; Zhu, Bin; Li, Guanyu
Abstract: In view of the defects of using deep learning method to identify named entities, which can't represent polysemy and doesn't contain context information, this paper proposes a new fusion model, which organically combines the bidirectional gated recurring neural network (BiGRU) and the dynamic graph edge evolutionary network (DGCNN) which are improved with attention mechanism. The time sequence features of the vector are captured by the improved BiGRU-ATT, and the local spatial features of the vector are enriched by DGCNN. Finally, fused output results are corrected and output by the constraint rules of CRF model, and the global optimal sequence is obtained by calculating the probability. The experimental results demonstrate that the proposed model is improved compared with the single model, which further highlights the superiority of the proposed fusion model.